2003
DOI: 10.1002/em.10142
|View full text |Cite
|
Sign up to set email alerts
|

Variability in human sensitivity to 1,3‐butadiene: Influence of the allelic variants of the microsomal epoxide hydrolase gene

Abstract: The carcinogenic effects of 1,3-butadiene (BD), a chemical widely used in the rubber industry, are thought to be due to its epoxide metabolites. In humans, these epoxides are detoxified predominantly by hydrolysis, a reaction mediated by the microsomal epoxide hydrolase (mEH) enzyme. The mEH gene is polymorphic and the most common mEH coding-region variants detected in human populations are the two amino acid polymorphisms Tyr113His and His139Arg. Polymorphic amino acid substitutions at residues 113 and 139 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 30 publications
(51 reference statements)
2
12
0
Order By: Relevance
“…In the present study, we examined this Y113H polymorphism in EPHX1 as well as another functional polymorphic variant at position 139 (H139R), so as to provide a more complete phenotypic picture of this important enzyme in BD metabolism. Abdel-Rahman et al have also recently performed a similar analysis in their study and have presented findings that support their earlier conclusion that EPHX1 polymorphisms influence BD genotoxicity in humans [30]. They reported that EPHX1 polymorphisms that are predicted to confer low EPHX1 activity elevated the HPRT variant frequency in workers exposed to >150 ppb BD by two-to three-fold in comparison to that found in workers with intermediate to high EPHX1 activity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the present study, we examined this Y113H polymorphism in EPHX1 as well as another functional polymorphic variant at position 139 (H139R), so as to provide a more complete phenotypic picture of this important enzyme in BD metabolism. Abdel-Rahman et al have also recently performed a similar analysis in their study and have presented findings that support their earlier conclusion that EPHX1 polymorphisms influence BD genotoxicity in humans [30]. They reported that EPHX1 polymorphisms that are predicted to confer low EPHX1 activity elevated the HPRT variant frequency in workers exposed to >150 ppb BD by two-to three-fold in comparison to that found in workers with intermediate to high EPHX1 activity.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, we found no effect of either genetic polymorphisms in EPHX1 or predicted EPHX1 activity on HPRT gene mutant frequency following BD exposure. The reasons for this difference are unclear, but the recent findings of Abdel-Rahman et al [30] are based on a comparison of only seven BD-exposed workers with low EPHX1 activities against nine with intermediate to high activity. Our negative findings are based upon a larger population comparing 27 BD-exposed workers with low activity against 12 with intermediate to high EPHX1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from examination of BD-exposed populations suggest that polymorphisms in GSTs might modulate the levels of DNA damage associated with BD exposure. It has been reported that SCE, CA, and MN frequencies were increased following DEB exposure in human lymphocytes carrying the GSTT1 (−) genotype; it was also found that the frequency of SCE was elevated in lymphocytes carrying the GSTM1 (−) genotype, which had been exposed to EB [33][34][35][36]. The GSTT1 gene has recently been identified as a possible biomarker of susceptibility to BD and its metabolites.…”
Section: Discussionmentioning
confidence: 95%
“…There are, however, other studies in humans showing a significant difference in levels of mutations and cytogenetic effects related to BD exposures (e.g., refs. 45,46). The large species difference in sensitivity to BD observed in the rodent cancer tests are according to the evaluation due to a difference in the metabolism to DEB.…”
Section: Discussionmentioning
confidence: 99%